Native plant abundance, diversity, and richness increases in prairie restoration with field inoculation density of native mycorrhizal amendments. (29th April 2020) - Koziol, Liz; Crews, Timothy E.; Bever, James D.
Abstract : Ecological restoration efforts can increase the diversity and function of degraded areas. However, current restoration practices cannot typically reestablish the full diversity and species composition of remnant plant communities. Restoration quality can be improved by reintroducing key organisms from the native plant microbiome. In particular, root symbionts called arbuscular mycorrhizal (AM) fungi are critical in shaping grassland communities, but are sensitive to anthropogenic disturbance, which may pose a problem for grassland restoration. Studies of mycorrhizal amendments include inoculation densities of 2–10, 000 kg of inocula per hectare. These studies report variable results that may depend on inocula volume, composition, or nativeness. Here we test eight different densities of native AM fungal amendment, ranging from 0 to 8, 192 kg/ha in a newly installed prairie restoration. We found that native plant establishment benefited from native mycorrhizal inocula, resulting in improvements in native plant abundance, richness, and community diversity. Moreover, the application of very low densities of native mycorrhizal inocula, as suggested on commercial mycorrhizal products, were ineffective, and higher concentrations were required to benefit native plant abundance and community diversity. These data suggest that higher densities of mycorrhizal amendment or perhaps alternative distribution methods may be required to maximize benefits of native mycorrhizal amendments in restoration practices.